Reflecting on meaning in an existential-reorientation group psychotherapy approach for cancer patients: A qualitative thematic analysis. Issue 3 (June 2022) - Grassi, Luigi; Sabato, Silvana; Caruso, Rosangela; Tiberto, Elisa; Padova, Silvia De; Ruffilli, Federica; Folesani, Federica; Nanni, Maria Giulia; Martino, Belvederi Murri; Zerbinati, Luigi; Testoni, Ines
Abstract: Objective: The objectives of this study were to evaluate, in the Italian cultural context, breast cancer patients' main meaning themes related to the experience of the disease, on the one side, and to be part of an existentially oriented group intervention, on the other. Method: A short reorientation-existential (RET) group intervention, structured by using some tools and background from cognitive analytic therapy (CAT) and based on the meaning-centered psychotherapy (MCP) existential framework, was delivered to 29 breast cancer patients. The sessions were audio-recorded and transcribed verbatim, with the narratives from reflective exercises (meaning of the journey cancer, meaning of the journey of intervention) uploaded to computer software NVivo 11. Analysis of the transcripts emerged from reflective exercises on the personal meaning of cancer and the letters of meaning (goodbye letter) written by the patients to express the meaning of their experience in the group was conducted through the interpretative phenomenological analysis (IPA) framework. Results: Four superordinate themes were identified in the exercise meaning of the experience of cancer, namely "sense of stigma and loneliness (the foreigner), " "guilt (unjust guilt and anticipatory guilt), " "reconsidering one's own life and nostalgia, " and "rebirth (a new life, life after life)." Three superordinate themes were found in the meaning of the group experience in the letters, namely "togetherness and gratitude, " "legacy, " and "acceptance." Significance of results: The study confirmed that a short group intervention, based on the existentially oriented framework and delivered in a public clinical healthcare setting, was enriched by focusing on the personal meaning of cancer. Some themes, such as loneliness, nostalgia, and rebirth, emerged during reflection giving, in written letters to participants, the sense of the group therapeutic experience.